From "East vs West" towards international multidisciplinary collaboration: An appraisal of lateral lymph nodes in rectal cancer. Issue 6 (9th August 2021) - Sluckin, Tania C.; Hazen, Sanne‐Marije J. A.; Kusters, Miranda
Abstract: Western and Eastern practices have traditionally differed in their approach to treating lateral lymph nodes in rectal cancer. While Western clinicians have primarily favored neoadjuvant (chemo)radiotherapy to sterilize lateral compartments, Eastern physicians have often opted for the surgical removed of lymphatic tissue with a lateral lymph node dissection without neoadjuvant treatment. The literature suggests similar oncological outcomes for these two separate techniques, while tangible differences exist. The combination of these paradigms may be beneficial in reducing overall morbidity while sustaining low recurrence rates. This article considers traditional Eastern and Western perspectives, discusses nodal features important for predicting malignancy and attempts to stimulate international, multidisciplinary consensus and collaboration. Abstract : Western clinicians have primarily favoured neoadjuvant (chemo)radiotherapy to sterilize lateral compartments, while Eastern physicians have often opted for the surgical removed of lymphatic tissue with a lateral lymph node dissection (LLND) without neoadjuvant treatment. However, tangible differences exist between these two paradigms and a combined technique may be beneficial in reducing overall morbidity while sustaining low recurrence rates. This article considers traditional Eastern and Western perspectives, discusses nodal features important for predicting malignancy and attempts to stimulate international, multidisciplinary consensus and collaboration.